Coronary artery bypass grafting in South Asian patients: Impact of gender. (August 2016) - Khan, Jamal Kabeer; Shahabuddin, Syed; Khan, Sheema; Bano, Gulshan; Hashmi, Shiraz; Sami, Shahid A.
Abstract: Background: Outcomes following Coronary artery bypass grafting (GABG) vary between genders, with females having a higher postoperative mortality than males. Most of the studies are on Caucasian or mixed population and it is postulated that Asian population and in particular women have higher morbidity and mortality. In this study we have compared outcomes of elective CABG in men and women of South Asian origin in terms of morbidity and mortality. Methods: From January 2006 to December 2012, 1970 patients underwent isolated elective CABG at the Aga Khan University Hospital, Pakistan were selected. The prospectively collected data was analyzed retrospectively including univariate and multivariate analysis to find the association of morbidity and mortality. Results: Among the study patients 1664 (85%) were male and 306 (15%) female. Hypertension and diabetes were the most common comorbid conditions seen preoperatively in female patients. Atrial fibrillation and sepsis were the most common postop complications seen in females. In hospital mortality was 3.9% in female underwent CABG as against 0.6% in male. Multivariate analysis showed older age, renal failure, dyslipidemia and prolonged cross clamp time as predictors of postoperative morbidity. Multivariate analysis showed female gender, age and renal failure as predictors of in hospital mortality. Conclusions: Female gender is an independent risk factor for postoperative mortality following CABG however, female gender is not found to be independent risk factor for morbidity. The trend of higher mortality in female patients was comparable to most studies done on Caucasian patients. Highlights: This paper gives an account of coronary artery bypass grafting (CABG) surgery performed in South Asian population with special attention to female gender. This is unique study as far as female patients are concerned in this part of the world. The female gender itself is a predictor of adverse outcome in terms of mortality. These results will help in preoperative counseling and suggests vigilant approach in perioperative care in female patients. It is heartening to note that the results are comparable to international standards.